Biosorpsi Kromium (Cr) Pada Limbah Cair Industri Elektroplating Menggunakan Biomassa Ragi Roti (Saccharomyces cerevisiae) - Shinta Elystia; Resna Rauda Putri; Sri Rezeki Muria (Jurnal Dampak, 2018)
Electroplating industry is one of the industries producing liquid waste containing heavy metals. Among the heavy metals contained in the liquid waste is Chromium (Cr) which has a high toxicity. One technology that can be applied to eliminate Cr metal in liquid waste is by the method Biosorption using biomass derived from yeast bread (Saccharomyces cerevisiae). This study aimed to study the ability of bread yeast biomass (saccharomyces cerevisiae) in removing Cr metal on variations in biosorbent weight of 0.25; 0.5 and 0.75 grams, mesh size 80; 100 and 140 and contact time 1; 2; 3 and 4 hours. The results showed that the highest Cr removing efficiency occurred at 0.75 g biosorbent weight at 80 mesh and 4 hours contact time with efficiency of 54.7%. The biosorption process indicates that the adsorption isotherm type obtained is Langmuir isotherms assumed that the layer formed is monolayer with R2 value of 0.8819. The SEM analysis results show the difference of the morphological shape on the sample surface before and after the biosorption process